2013
DOI: 10.3133/sim3212
|View full text |Cite
|
Sign up to set email alerts
|

Paleoseismology of a newly discovered scarp in the Yakima fold-and-thrust belt, Kittitas County, Washington

Abstract: M o u n t a i n s B o y l s t o n B a d g e r P o c k e t A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…But lacking extensive field investigations of the NNE striking faults, it is not clear if these faults are dip slip or strike slip or some combination therein. In the one extant trenching study, the northeast striking Boyleston Ridge scarp (Figure ) showed faulting that juxtaposed Quaternary strata against Columbia River Basalt Group on a steep reverse fault with an indeterminate strike‐slip component (Barnett et al, ). Although these north‐to‐northeast striking faults occur within the backarc area for which there is contemporary GPS data suggesting regional clockwise rotation (McCaffrey et al, , ), without knowledge of what kind of faults they are, it remains uncertain if movement on these faults could result in regional clockwise rotation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But lacking extensive field investigations of the NNE striking faults, it is not clear if these faults are dip slip or strike slip or some combination therein. In the one extant trenching study, the northeast striking Boyleston Ridge scarp (Figure ) showed faulting that juxtaposed Quaternary strata against Columbia River Basalt Group on a steep reverse fault with an indeterminate strike‐slip component (Barnett et al, ). Although these north‐to‐northeast striking faults occur within the backarc area for which there is contemporary GPS data suggesting regional clockwise rotation (McCaffrey et al, , ), without knowledge of what kind of faults they are, it remains uncertain if movement on these faults could result in regional clockwise rotation.…”
Section: Discussionmentioning
confidence: 99%
“…Mapping, interpretation of lidar imagery, and analysis of aeromagnetic data all indicate a secondary set of faults, shorter in length, that are nearly perpendicular to the west‐northwest trending regional structure. Near the Manastash anticline, faults oriented nearly perpendicular to the anticlinal trend include the ~4 km long Boyleston Ridge fault (Barnett et al, ; Blakely et al, ) (Figure a) and faults on the backlimb of Manastash anticline (Figure c). In some cases, magnetic lineaments that trend northerly (Figure ) are clearly associated with north‐northeast striking faults (Blakely et al, ), and an example is the north‐northeast trending magnetic lineaments that are associated with the 0.7–1.3 km long faults in bedrock on the backlimb of the Manastash anticline (compare inset in Figure a to Figure c).…”
Section: Manastash Anticline: Geometry and Structuresmentioning
confidence: 99%